Comparative evaluation of intravenous versus intranasal dexmedetomidine on emergence delirium and hemodynamics in pediatric patients undergoing adenotonsillectomy: a randomized controlled trial - Dai, Chenxu; Zhao, Xuemei; Li, Aoxue; Zhang, Xuedong; Wang, Penglei; Zhang, Ye; Wu, Yun (Frontiers in Pharmacology, 2025)
BackgroundDexmedetomidine effectively prevents emergence delirium in children. However, intravenous dexmedetomidine is frequently associated with hemodynamic instability and delayed recovery. Intranasal dexmedetomidine has been proposed as a method of reducing these side effects. This study aimed to evaluate the effects of intranasal versus intravenous dexmedetomidine on emergence recovery and hemodynamics in children undergoing adenotonsillectomy.MethodsA total of 139 children, aged 3–10 years, who were scheduled for elective adenotonsillectomy were randomly assigned to receive intravenous dexmedetomidine (IV DEX group) or intranasal dexmedetomidine (IN DEX group), or saline (control group) after anesthesia induction. The primary outcome was the highest score on the pediatric anesthesia emergence delirium (PAED) score during the first 30 min after awakening. Secondary outcomes included the perioperative blood pressure and heart rate, time to awakening, postoperative pain score, and length of post-anesthesia care unit (PACU) stay.ResultsThe highest PAED and pain scores were significantly lower in the IV and IN DEX groups than those in the control group during the first 30 min after awakening. However, no significant differences were observed between the IV and IN DEX groups. Notably, patients in the IN DEX group exhibited a significantly lower PAED score at 2 h and lower pain scores at 2, 4, and 6 h postoperatively than those in the IV DEX group. Patients in the IV DEX group exhibited a significantly longer awakening time and length of PACU stay than those in the IN DEX and control groups. In the IV DEX group, the heart rate was significantly lower perioperatively than at baseline, while this effect was not observed in the IN DEX group.ConclusionBoth intravenous and intranasal administration of dexmedetomidine after induction of anesthesia effectively improved emergence delirium and pain intensity in children undergoing adenotonsillectomy. Intranasal administration of dexmedetomidine provided more stable hemodynamics and more prolonged analgesia and sedation than intravenous infusion of dexmedetomidine.Clinical Trial Registrationhttps://www.chictr.org.cn/showproj.html?proj=180658.